Peach Gum Polysaccharide as an Additive for Thermoplastic Starch to Produce Water-Soluble Films - Juan Vicente Miguel Guillem; Andrea Juan-Polo; Cristina Pavon; Juan López-Martínez (Macromol)
Thermoplastic starch (TPS) has gained considerable attention during the last few years in developing starch-based biodegradable food packaging materials or edible coatings due to its high availability and low cost. TPS is manufactured from starch plasticized with food-grade plasticizers, making it suitable for food contact applications. In addition, TPS is bio-based and biodegradable, which, from an environmental perspective, closes the circle of the circular economy. However, the industrial application of TPS is somewhat limited due to its poor mechanical performance and low water resistance. However, the low water resistance could increase the water sensitivity of TPS, which could be advantageous for coating application or food encapsulation. The present work aims to tailor the water sensitivity of TPS by adding peach gum polysaccharide to obtain water-soluble films. With this aim, peach gum polysaccharide (PGP) was extracted from peach gum (PG) using the thermal hydrolysis method. Films of TPS-PG and TPS-PGP were prepared and characterized by their water sensitivity and mechanical, microstructural, and thermal properties. The results show that PGP allows the obtaining of films with water sensitivities higher than 70% but also improves TPS elongation at break, making the material more suitable for application as film.